Sociology for everyone (Boston Pearson Education, 2011)
A comprehensive introduction to sociology, examining such aspects as family life, politics, inequality, and social control. Includes self-examination questions, discussion topics, and suggested projects.
Published in association with Basil Blackwell, Cambridge, MA, USA.
Includes bibliographical references (p. [347]-358) and index.
Keywords: Sociology; Sociology